Management of diabetes mellitus through teleconsultation during COVID-19 and similar scenarios - Guidelines from Indian Council of Medical Research (ICMR) expert group. Issue 5 (September 2021) - Sarveswaran, Gokul; Rangamani, Sukanya; Ghosh, Amerta; Bhansali, Anil; Dharmalingam, Mala; Unnikrishnan, Ambika Gopalakrishnan; Kishore Vikram, Naval; Mathur, Prashant; Misra, Anoop
Abstract: Introduction: Emergence of COVID-19 pandemic has led to increased use of telemedicine in health care delivery. Telemedicine facilitates long-term clinical care for monitoring and prevention of complications of diabetes mellitus. Guidelines: Precise indications for teleconsultation, clinical care services which can be provided, and good clinical practices to be followed during teleconsultation are explained. Guidance on risk assessment and health education for diabetes risk factors, counselling for blood glucose monitoring, treatment compliance, and prevention of complications are described. Conclusion: The guidelines will help physicians in adopting teleconsultation for management of diabetes mellitus, facilitate access to diabetes care and improve health outcomes. Highlights: Framework of teleconsultation for diabetes managment during COVID-19 pandemic and its aftermath is given based on expert consensus. Indication to use teleconsultation for diabetes patients vis-a vis management by face to face consultation has been defined. Steps to be followed by physicians/patients during teleconsultation of individuals with diabetes mellitus are listed.